Новые клещи-фитосейиды (Parasitiformes, Pliytosiidae) из Туркмении - Колодочка, Л.А. (Вестник зоологии, 1982)
Three species of phytoseiid mites collected on different host plants in the Turkmen S S R are described as new. Amblyseius turangae sp. n., closely allied to A. luppovae W a i n s t e i n ,1962, is distinct i nthe shape of spermatheca, decidedly larger proximal teeth of fixedcheliceral digit, almost egual length of PM, and PMs setae, long macroseta on tarsus IV, the pre- sence of a single pair of closely disposed setae on tibia III. Anthoseius (s. str.) juniperisp. n., similar to A. (s. str.) victorovi W a i n s t e i n , 1975, differs from it in the lack ofa n a lpores o nthe ventrianal shield, in the shape of the spermatheca, remarkably shorter setat P L and D6. Anthoseius (Amblydromellus) tamaricis sp. n., closely related to other species of the subgenus and havinglong macroseta ontarsus IV, differs in tubuliformspermatheca. As distinct from A. (A.) kazachstanicus ( W a i n s t e i n , 1958) and A. (A.) khosrovensis (Arut unjan, 1971), the new species has longperitremes; it is also characteristic with a single tooth on the movable cheliceral digit, while A. (A.) involutus ( L i v s c h i t z et Kuznetzov, 1972), cerasicolus Wainstein et Vartapetov, 1973 and A. (A.) hadzhievi (Abbasova,1970) have two teeth. Habitat data for other six species are reported first found on plants in the Turk- men SSR.